The Key To Success For 'Kefi' Coffee Shop In The New Normal Era: An Analysis of Adaptive Strategies - Wilujeng, Aura Masdena Nur; Ambarwati, Rita (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim: This study aims to analyze the implementation of adaptive strategies in Coffe Shop